Position-related differences in selected morphological body characteristics of top-level handball players - Sibila, M.; Pori, P. (Collegium Antropologicum, 2009)
We aimed to establish the main morphological characteristics of Slovenian junior and senior national handball team players. Morphological characteristics for various player subgroups (goalkeepers, wings, back players and pivots) were also determined so as to establish whether they had distinct profiles. The subjects were 78 handball players who were members of the Slovenian junior and senior national team in the period from 2000 to 2007. A standardised anthropometric protocol was used to assess the subjects` morphological characteristics. The measurements included 23 different anthropometric measures. Data were processed with the SPSS computer programme. First, basic statistical characteristics of anthropometric measures were obtained for all subjects together and then for each group separately. Somatotypes were determined using Heath-Carter`s method. Endomorphic, mesomorphic and ectomorphic components were calculated by computer on the basis of formulas. In order to determine differences in the body composition and anthropometric data of the subjects playing in different positions, a one-way analysis of variance was employed. The results show that on average the wings differ the most from the other player groups in terms of their morphological body characteristics. The values of their body height, body mass and the quantity of subcutaneous fat are statistically significantly lower than those of players in the other groups. Goalkeepers are relatively tall, with high values of body mass and low values of transversal measures. Their skin folds are the most pronounced among all groups on average and their share of subcutaneous fat in total body mass is the highest. Consequently, their endomorphic component of the somatotype is pronounced. Pivots and back players are becoming increasingly similar in terms of their morphological body characteristics. Pivots maintain greater robustness, have a higher quantity of muscle mass as well as more pronounced transversal measures and a mesomorphic component of the somatotype. The results of our study confirm that groups of handball players occupying different positions differ amongst themselves in terms of many measurements. This is a result of specific requirements of handball play which are to be fulfilled by players.